The Effect of CaCl2 as The Cross Linked Agent on Physic and Chemistry Properties of Whey Protein Edible Film - Manik Eirry Sawitri; Abdul Manab; Siti Khoirul Zanah (Faculty of Animal Science Universitas Brawijaya, 2008)
TheÂ aim of this research was to know effect percentage CaCl2 addition as the cross linked agent on physic and chemistry properties of whey protein edible film. The design of this research was completely randomized design, consisted of four treatments: C1 (CaCl2 0.15%), C2 (CaCl2 0.20%), C3 (CaCl2 0.25%) and C4 (CaCl2 0.30%) which each treatment had three repetitions. The variables were water vapor permeability (wvp), protein solubility, microstructure and electroforetic. The result showed that there was highly significant effect (P<0.01) of the addition CaCl2 on the wvp and protein solubility. C2 treatment gave lower wvp value and protein solubility. CaCl2 addition gave structure of edible film look like porous and not flat on its surface. The electroresis look occured at band more thin with molecular weight 14-18 kDa. Â Keywords: edible film whey prtein, CaCl2